Características termorreguladoras no início da gestação e índices reprodutivos de matrizes suínas de diferentes ordens de parto - Vieira, Paula Borges (2012)
The aim of this study was to evaluate thermoregulatory characteristics in early pregnancy as well as some reproductive efficiency of sows of different parity orders. It was collected and analyzed rectal and skin temperatures and respiratory rate of 98 sows of four groups of parity orders: gilts, primiparous, second to sixth and seventh to eleventh parity order, as well as the during pregnancy and the number of piglets born alive of 164 sows, which were compared to four groups of parity orders, in three moments of early pregnancy. The mean values of respiratory rate and skin temperature did not differ between parity orders. Rectal temperature of 7th to 11th parity order was lower than all other parity orders, probably because these animals are older, so they have a slower metabolism than the others. This group of parity order also showed a higher during pregnancy. In early pregnancy, age does not affect the respiratory rate and skin temperature, however, older sows have a lower rectal temperature, as well as higher gestation period.